2002
DOI: 10.1053/euhj.2001.3156
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of continuous positive airway pressure and standard oxygen therapy in acute pulmonary oedema. Effects on plasma brain natriuretic peptide concentrations

Abstract: CPAP produces a more rapid clinical and symptomatic improvement in patients with acute pulmonary oedema, particularly within the first hour. CPAP is a useful adjunctive treatment in the early management of acute heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 36 publications
4
47
0
3
Order By: Relevance
“…An improvement in RR and symptoms of respiratory fatigue (improved breathing pattern, decreasing intercostal suprasternal retraction and subjective respiratory distressed) when coupled with improved oxygenation, and lower PaCO 2 is considered as indirect objective evidence of decrease work of breathing, dyspnea, and alveolar hypoventilation [15,31]. These confirm that the therapeutic intervention in our study was delivered successfully and appropriately.…”
Section: Discussionsupporting
confidence: 70%
“…An improvement in RR and symptoms of respiratory fatigue (improved breathing pattern, decreasing intercostal suprasternal retraction and subjective respiratory distressed) when coupled with improved oxygenation, and lower PaCO 2 is considered as indirect objective evidence of decrease work of breathing, dyspnea, and alveolar hypoventilation [15,31]. These confirm that the therapeutic intervention in our study was delivered successfully and appropriately.…”
Section: Discussionsupporting
confidence: 70%
“…1,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The benefits of inhospital NIPPV have been confirmed through metaanalyses. In a systematic review and meta-analysis of NIPPV in acute cardiogenic pulmonary edema, Masip et …”
Section: In-hospital Noninvasive Positive Pressure Ventilationmentioning
confidence: 71%
“…The majority of NIPPV studies have focused on patients with acute pulmonary edema. [6][7][8][9]11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26]29,31,32,35,[38][39][40][41] However, NIPPV may prove useful with other reversible disease processes such as chronic obstructive pulmonary disease or asthma exacerbations. 33,42,43 While utilized in in-hospital practice, the role of NIPPV for pneumonia-associated respiratory failure is less clear.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…This is supported by one study (3) that showed noninvasive positive pressure ventilation therapy was associated with worse outcomes when given in preference to vasodilator therapy. None of these slightly different types of assisted ventilation have been shown to be superior to any other and studies of these modalities are ongoing (4)(5)(6)(7). These therapies should be considered primarily when the patient is hypoxic with SaO 2 of less than 90% (5).…”
Section: Assisted Ventilationmentioning
confidence: 99%